Robust mica perovskite photoelectric resistive switching memory. (February 2023) - Zhang, Guanglei; Xu, Yanqing; Yang, Shuai; Ren, Shuxia; Jiao, Yinan; Wang, Ye; Ma, Xuena; Li, Hao; Hao, Weizhong; He, Caili; Liu, Xiaomin; Zhao, Jinjin
Abstract: Metal halide perovskites have attracted considerable attention for use in flexible resistive random access memory (RRAM), due to their good photoelectric regulation, high ON/OFF ratios, and low fabrication costs. Flexible conductive substrates play a crucial role in improving RRAM device performance. Herein, mica/silver nanowires welded with aluminum-doped zinc oxide (mica/AgNWs@AZO) substrates with high-temperature resistance, high flexibility, high conductivity, and good stability have been successfully fabricated. The average sheet resistance 3.5 Ω sq −1 of the conductive mica substrate is 68% lower than that of a commercial PET/ITO, and it remains stable below 13.1 Ω sq −1 under 200 °C. The maximum conductivity of the mica/AgNWs@AZO substrate can reach 58 S/m after 64 h of tensile stress bending at a radius of 20 mm. Perovskite CsPbBr3 nanocrystal (NC) RRAM is constructed on the mica/AgNWs@AZO substrate. The ON/OFF ratio 10 3 of the device in light is 10 2 times higher than that in dark under 5000 bending cycles. Flexible perovskite RRAM is a promising candidate for next-generation-logic, adaptive, non-volatile memory devices. Graphical Abstract: A flexible, robust, high-efficiency photoelectric resistive switching memory of conductive mica-based CsPbBr3 perovskite is fabricated and exhibits high mechanical stability. ga1 Highlights: The sheet resistance of the conductive mica-based substrate remains stable below 13.1 Ω sq −1 under 200 °C. The conductivity of the conductive mica-based substrate can reach 58 S/m after 64 h of tensile stress bending at a radius of 20 mm. The ON/OFF ratio of the mica perovskite resistive random access memory in light is 10 2 times higher than that in dark under 5000 bending cycles.